Wspomaganie zarządzania w jednostkach administracji publicznej - Grzybek, Jerzy; Mazur, Paweł; Mazur, Zygmunt (Support of Management in E-Government, 2005)
The work presents basic problems in management in e-government with emphasis on information delivery to managers, when this information has a significant impact on making decisions. It also treats about data exchange standards and the current state of preparation of the Polish administration for the idea of the information society.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 167-173